Preharvest calcium applications improve postharvest quality of papaya fruits (Carica papaya L. cv. Eksotika II) - Madani, Babak; Mirshekari, Amin; Sofo, Adriano; Tengku Muda Mohamed, Mahmud (Taylor & Francis Group, 2016)
This research was conducted to evaluate the effects of calcium chloride (CaCl2) and calcium nitrate Ca(NO3)2 on nutrient concentrations and postharvest quality of papaya fruits. In the first experiment, plant stem height increased significantly after Ca(NO3)2 application compared to CaCl2. The calcium content in the peel and pulp for both sources [CaCl2 and Ca(NO3)2] significantly rose with increasing calcium concentrations, but there was a significantly higher content of calcium in fruit peel and pulp in the CaCl2 treatment. Magnesium and potassium in fruits decreased with increasing calcium concentrations. A reduction in anthracnose lesion diameter in the infected fruit with increasing calcium was observed in both CaCl2 and Ca(NO3)2 treatments. Ethylene production in fruits decreased with increasing calcium concentrations. In the second experiment, only CaCl2 was used as the calcium source, and results showed that the calcium content in fruit peel and pulp significantly increased at higher CaCl2 levels, whereas ethylene production, anthracnose lesion diameter, and magnesium content decreased compared to control.